Simulating "Peripheral Harm" as an AMBER Alert Issuance Criterion: Implications for Anticipating Threats to Child Safety. (August 2017) - Williams, Joshua H.; Griffin, Timothy; Miller, Danielle; Wooldredge, John
Although there is some limited research on the effectiveness of the America's Missing: Broadcast Emergency Response (AMBER) Alert system, to date, there has been no research specifically examining the viability of prospective AMBER Alert issuance criteria. Using data acquired from various media accounts of 446 AMBER Alerts issued in the United States and Canada, we examine how well "peripheral harm" (harm to someone other than the abducted child during the course of the abduction) predicts subsequent harm to the abducted child. Counterintuitively (from the perspective of AMBER Alert issuance decision making), peripheral harm or threat is negatively associated with harm to the victim in cases involving an AMBER Alert. Furthermore, this negative finding is spurious, and is primarily driven by the fact that, disproportionately, the abductors who commit "peripheral harm" in AMBER alert cases are parents and other family members of the child who are presumably unlikely to harm child relatives despite whatever violence they might commit (or threaten) against others. We discuss the implications for the use of peripheral harm as an AMBER Alert issuance criterion, the empirical evaluation of the system, and the public discourse surrounding the AMBER Alert system and its relationship to child protection in general.